Revelation 1-3 in Christian Arabic commentary: John's first vision and the letters to the seven churches - Davis, Stephen J. (Christian Arabic Texts in Translation, 2019)
Frontmatter -- Contents -- Preface and Acknowledgments -- Editorial Notes and Abbreviations -- Introduction: Two Arabic Commentaries on the Apocalypse of John in Historical and Cultural Context -- 1 Būlus al- Būshī on Revelation 1–3: Christology and Christian- Muslim Encounter -- 2 Ibn Kātib Qayṣar on Visions, Angels, Prophets, and Dreams -- 3 Ibn Kātib Qayṣar on Revelation 1–3: The First Vision and the Letters to the Seven Churches -- 4 Būlus al- Būshī, Commentary on the Apocalypse of John, ch. 1–3 -- 5 Ibn Kātib Qayṣar, Commentary on the Apocalypse of John, ch. 1–3 -- Works Cited -- Subject Index -- Biblical Index